2018
DOI: 10.1002/cmdc.201800158
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pyrazoles as Phenol Surrogates to Yield Potent Inhibitors of Macrophage Migration Inhibitory Factor

Abstract: Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine that is implicated in the regulation of inflammation, cell proliferation, and neurological disorders. MIF is also an enzyme that functions as a keto-enol tautomerase. Most potent MIF tautomerase inhibitors incorporate a phenol, which hydrogen bonds to Asn97 in the active site. Starting from a 113-μm docking hit, we report results of structure-based and computer-aided design that have provided substituted pyrazoles as phenol alternatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…93,108 Our lab has recently shown that a pyrazole ring can serve as an alternative to the phenol that may overcome some of the metabolic concerns associated with phenols. 110 Lys-32, which is located near the rim of the active site, has been shown in crystal structures to form multiple hydrogen bonds with ligands, though it was recently found that there may be a limit to the benefits of increased coordination number of the ammonium side chain. 139 Specifically, the naphthyridinone 21 (Figure 6) was found to have similar K i and K d values as related quinolines such as 20 in spite of an added hydrogen bond from Lys-32 to the carbonyl oxygen atom, as seen in crystal structures.…”
Section: Modes Of Inhibition: a Closer Lookmentioning
confidence: 99%
“…93,108 Our lab has recently shown that a pyrazole ring can serve as an alternative to the phenol that may overcome some of the metabolic concerns associated with phenols. 110 Lys-32, which is located near the rim of the active site, has been shown in crystal structures to form multiple hydrogen bonds with ligands, though it was recently found that there may be a limit to the benefits of increased coordination number of the ammonium side chain. 139 Specifically, the naphthyridinone 21 (Figure 6) was found to have similar K i and K d values as related quinolines such as 20 in spite of an added hydrogen bond from Lys-32 to the carbonyl oxygen atom, as seen in crystal structures.…”
Section: Modes Of Inhibition: a Closer Lookmentioning
confidence: 99%
“…It is proposed that human MIF is a good test system for such work owing to its moderate size and to the availability of multiple high-resolution crystal structures as well as accurate binding data for numerous, diverse inhibitors. 21,22,30 ASSOCIATED CONTENT Supporting Information. This information is available free of charge on the ACS Publications website at http://pubs.acs.org.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF) is both a keto-enol tautomerase and a cytokine associated with inflammatory diseases and cancer. 21,22 It was selected as the subject of this study since it has many characteristics that make it a suitable benchmark system: (1) the trimeric protein has moderate size with 342 residues; (2) multiple high-resolution crystal 4 structures of complexes of MIF with tautomerase inhibitors are available; (3) the crystal structures for many inhibitors show modest conformational changes for binding-site residues;…”
Section: Introductionmentioning
confidence: 99%
“…[27,29] Furthermore,t he Jorgensen lab discovered potent MIF inhibitors that contain ab iaryltriazole or pyrazole scaffold. [30,31] However,t he potencyt oi nhibit MIF tautomerase activity does not always correlate well with the potencyt oi nhibit the MIF-CD74 interaction or MIF induced signaling in cell-based studies. [32,33] Altogether,this suggests that development of molecules that merely bind to the tautomerase enzyme active site may not be enough to effectively interfere with MIF protein-protein interactions.I na ddition, proteasome-dependent MIF degradation induced by HSP90 suppression proved to be correlated with the inhibition of MIF activity on cell proliferation.…”
Section: Introductionmentioning
confidence: 99%